Kebijakan Formulasi Tindak Pidana Penodaan Agama Dari Perspektif Hukum Pidana Di Indonesia - Demi Hadiantoro; Gunarto Gunarto; Lathifah Hanim (UNISSULA Semarang, 2020)
Indonesia is a God-given country and has a philosophy of the Godhead, therefore realizing the peace of religious life is a legal interest as well as public interest that is duly protected. Thus the legal protection of the existence of legal interest for every citizen, then the provisions on blasphemy of religion should be regulated and protected in criminal law. Based on the above ideas then it can be formulated some problems that is how the current criminal law formulation policy in an effort to overcome religious blasphemy. And what is the future criminal law formulation policy towards the prevention of religious blasphemy in the framework of reform of criminal law in Indonesia. This research is analytical descriptive research with normative juridical approach. The data used are secondary data in the form of primary legal materials, secondary legal materials, tertiary law materials hence data collection techniques used are literature study and documentary of secondary data that has been analyzed. From the result of the research, it can be concluded that the current criminal law used in the effort to overcome the blasphemy is the Criminal Code (KUHP) but contains some weaknesses in the substance of the regulation ie blasphemy is categorized as a crime against public order and there is disharmony between status and explanation staining with text or staining formulation. The effort to overcome the blasphemy of religion in the concept of KUHP 2005 is formulated as a crime against religion and related to religion or to religious life. The upcoming criminal law formulation which specifically regulates the blasphemy of religion should be formulated by considering the integration of religious blasphemy in the concept of the Indonesian Criminal Code 2005 by considering the following matters: 1) the harmonization of material / substance of crime, 2) formulation policy of criminal responsibility, and 3) formulation policy of criminal system and punishment. Keywords: Formulation Policy, Desecration Of Religion, Legal Perspective